2022
DOI: 10.3390/biom12060779
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Reveals That HMGB1 Induces Macrophage Polarization Different from Classical M1

Abstract: Macrophages are key inflammatory immune cells that display dynamic phenotypes and functions in response to their local microenvironment. In different conditions, macrophage polarization can be induced by high-mobility group box 1 (HMGB1), a nuclear DNA-binding protein that activates innate immunity via the Toll-like receptor (TLR) 4, the receptor for advanced glycation end products (RAGE), and C-X-C chemokine receptor (CXCR) 4. This study investigated the phenotypes of murine bone-marrow-derived macrophages (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…IL-6 is secreted mainly by monocytes/macrophages specifically when polarized to an M1-like phenotype. It was demonstrated also that HMGB1 may polarize macrophages via Toll-like receptor (TLR) 4 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is secreted mainly by monocytes/macrophages specifically when polarized to an M1-like phenotype. It was demonstrated also that HMGB1 may polarize macrophages via Toll-like receptor (TLR) 4 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…found that exogenous lactate has deleterious effects on sepsis patients by mediating the lactylation and acetylation modifications of HMGB1 in macrophages, inducing the release of lactylated/acetylated HMGB1 from cells by exosomal secretion ( 102 ). As an important damage associated molecular pattern (DAMP) molecule, HMGB1 induces macrophage polarization toward the M1 phenotype while maintaining migratory capacity and some M2 characteristics ( 103 ). Subsequently, Du S et al.…”
Section: Lactylation Modifications Are Involved In Regulating Macroph...mentioning
confidence: 99%
“…In the same aspect, loss of HMGB1 in macrophages can increase the differentiation of proinflammatory macrophages and enhance inflammatory response under specific conditions, not the otherwise ( 140 ). In this regard, HMGB1 may induce distinct macrophage phenotypes probably due to different redox isoforms ( 141 ). Besides HMGB1, the expression level of several members of HSPs is closely related to distinct stages of polarization in macrophages ( 142 ).…”
Section: Polarization and Phenotype Of Macrophagesmentioning
confidence: 99%